2014
DOI: 10.4082/kjfm.2014.35.3.119
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise on Prevention of the Common Cold: A Meta-Analysis of Randomized Controlled Trial Studies

Abstract: BackgroundBecause there is no specific treatment for the common cold, many previous studies have focused on prevention of the common cold. There were some studies reporting that regular, moderate-intensity exercise increases immunity and prevents the common cold. We conducted a meta-analysis to determine the effects of exercise on prevention of the common cold.MethodsWe searched MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials (CENTRAL), CINAHL for studies released through June 2013. We manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 12 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…In this study, regular physical exercise was also found to be a protective factor against the incidence of ILI. A recent meta-analysis of four studies obtained similar results that regular, moderate-intensity exercise may have an effect on the prevention of the common cold, and the risk of the common cold in exercise group was 27% lower as compared to the control group [ 10 ]. The protective effects of regular physical exercise on these infectious diseases may be partially explained by enhanced activity of several immune parameters that could be important in limiting or clearing viral infection [ 11 ].…”
Section: Discussionmentioning
confidence: 92%
“…In this study, regular physical exercise was also found to be a protective factor against the incidence of ILI. A recent meta-analysis of four studies obtained similar results that regular, moderate-intensity exercise may have an effect on the prevention of the common cold, and the risk of the common cold in exercise group was 27% lower as compared to the control group [ 10 ]. The protective effects of regular physical exercise on these infectious diseases may be partially explained by enhanced activity of several immune parameters that could be important in limiting or clearing viral infection [ 11 ].…”
Section: Discussionmentioning
confidence: 92%
“…Second, Lee et al 1) ignored our large cohort study which found that physical activity at work, and at leisure, had no association with the common cold risk when adjusted for potential confounders. 4) We analyzed the relationship between leisure time physical activity and common cold incidence in 3,470 males who were followed up for 2 years.…”
mentioning
confidence: 95%
“…Lee et al 1) carried out a meta-analysis of the potential role of exercise in preventing the common cold, and calculated that exercise might reduce the incidence of colds by 27% (relative risk [RR], 0.73; 95% confidence interval [CI], 0.56 to 0.95). However, their study has important limitations.…”
mentioning
confidence: 99%
See 2 more Smart Citations